“Brown v. Board of Education was the Beginning”: The School Desegregation Cases in the United States Supreme Court: 1954-1979 - Philip B. Kurland (Washington University Law Quarterly, 1979)
A retrospective look at the Supreme Court's efforts in the field of school desegregation may at least reveal something about how the Court works and about the limitations of the judicial process.
Keywords: Schools and school districts; Segregation; Discrimination; United States -- Supreme Court